The Application Of Educational Accounting In Facing Work Challenges At Industry 4.0 For Modern Accountant - Novita Aprilia; Evelyn Febrina Ret Herdyane (CV Pena Jaya Pers, 2024)
This study aims to examine the application of educational accounting in facing work challenges at Industry 4.0 for modern accountants. The research used by researchers is a Systematic Literature Review with data obtained from journals and research articles from 2020-2023. The data source platform used in this study is Google Scholar. The results of this study indicate that business development is currently in the Industrial Revolution 4.0 stage focusing on developing digital-based business processes and products. So that in the process higher education is not just a place, where students gain knowledge and skills but also a provision for students to complete the industrial era, especially the role of accounting education in it. Based on the study it was found that technological developments, such as AI, will have a significant impact on professional accounting services in the future. There is a need for new skills and knowledge required to deal with this change. The conclusions from the analysis carried out are; the strength that can be developed is that human analytical skills are still very much needed even though some of the accountant jobs will be replaced automatically. The opportunities that exist are several accounting professions that still exist despite technological changes.